2019
DOI: 10.5539/gjhs.v11n9p52
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Periodontal Diseases and Oral Hygiene Status Among Community-Dwelling Adults With Physical Disabilities in Thailand: A Cross-Sectional Study

Abstract: OBJECTIVE: There is limited evidence concerning oral health among disabled people capable of independently performing oral hygiene practices. This study investigated factors associated with periodontal diseases and oral hygiene status among community-dwelling, working-age Thai adults with physical disabilities. MATERIAL & METHODS: A cross-sectional study was conducted between 1st February to 15th March 2018 at the Community Center for Independent Living, a disability community club locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
(31 reference statements)
1
5
2
1
Order By: Relevance
“…Following the program, all participants received a leaflet containing oral hygiene instructions, an oral health care self‐education video, and a booklet on the Thai Universal Healthcare Coverage (UHC) plan of dental care benefits and limitations. Thai citizens with disabilities are eligible to receive primary dental care services, including preventive dentistry, fluoride therapy, dental prophylaxis, tooth extraction, tooth filling, and removable acrylic dentures 5 . However, the UHC plan includes out‐of‐pocket expenses for uncovered dental treatments such as root canal treatments and metal crowns.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the program, all participants received a leaflet containing oral hygiene instructions, an oral health care self‐education video, and a booklet on the Thai Universal Healthcare Coverage (UHC) plan of dental care benefits and limitations. Thai citizens with disabilities are eligible to receive primary dental care services, including preventive dentistry, fluoride therapy, dental prophylaxis, tooth extraction, tooth filling, and removable acrylic dentures 5 . However, the UHC plan includes out‐of‐pocket expenses for uncovered dental treatments such as root canal treatments and metal crowns.…”
Section: Methodsmentioning
confidence: 99%
“…There is considerable evidence that people with disabilities are in worse overall health and have poorer oral health than people without disabilities 2–4 . A prior study from Thailand reported that physical disabilities are related to insufficient oral hygiene practices among individuals with mobility impairments and hand function limitations 5 . Although these individuals can perform routine oral hygiene self‐care, they may experience specific problems during brushing teeth; for example, high muscle tone leading to unwanted movements, decreased balance control, and lack of concentration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…TOFHLiD ölçüm aracı temel alınarak geliştirilen ölçüm araçları, okuma, okuduğunu anlama, sayısal beceri boyutunu ölçmektedir (17,23,37,38,44,48,53,55,56,59). HeLD ölçüm aracı temel alınarak geliştirilen ölçüm araçları okuyabilme, okuduğunu anlama ve sayısal beceri boyutlarını ölçmektedir (41,42,52,57). Araştırmalar içerisinde ADS bilgisi ya da kapsamlı ADSOY boyutunda ölçüm yapan araştırma sayısı sınırlıdır ve karar verme boyutunu içeren ölçüm aracı sayısı sekizdir.…”
Section: öLçüm Boyutlariunclassified